An Investigation on the determinants of effective internal audits in the Kogi State in Nigeria - Samir Ikoojo, IkoojoAbu Bakar Muhammed (2017)
The objective of this study is to investigate the factors affecting internal audit effectiveness (IAE) in the Kogi State public service. Hence, this study employed a quantitative method through Random sampling method. To achieve the objectives of the study, the target sample size for this research were (132) internal auditors and (110) executives with total of (242). However, 363 questionnaires were distributed by adding up 50% to the (242) total for both respondents, which were distributed across the 15 ministries for the current study. Consequently, a total of (118; 86) for both internal auditors and executives respectively, summing up to (204) questionnaires were retained for analysis for both. The data was analyzed with the use of Partial Least Square Structural Equation Modeling (PLS-SEM). The result of the study showed the relationship effects of management support, audit objectivity, audit independence, audit staff competency, quality of audit and career and advancement, with the IAE within the Kogi State public service. According to the findings of the result, management support has significant and positive contribution for the internal audit effectiveness, audit objectivity has significant and positive relationship with IAE, audit staff competency has positive and significant relationship with IAE, quality of audit work has positive and significant relationship with IAE. While the other two variables: audit independence and career and advancement did not support the hypotheses. Although four out of the six independent variables used for this study provided 46.1% of the contributions for IAE in the Kogi State public service, the variables have collective significance in identifying any non-compliance activities and add values for the IAE in the Kogi State public service.